Model-based evidence of the dominance of the guitar brace design over material and climatic variability for dynamic behaviors. (November 2021) - Viala, Romain; Placet, Vincent; Cogan, Scott
Highlights: Evidence of the dominance of the guitar brace design over material and climatic variability. Statistical methodology applied to musical instruments study. Stochastic analysis based on physics-based models. Fuzzy FRF for different cases of soundboard braces. Abstract: It is generally alleged that the design choices of acoustic guitar bracing patterns lead to a specific sound of the instrument. However, in the presence of strong uncertainties due to variability of material properties and climatic conditions, the robustness of the soundboard dynamics has yet to be investigated. In this study, three types of bracing patterns are studied using physics-based models and stochastic analyses are performed to account for material and climatic uncertainties. It is shown that the choice of a brace design leads, at least in the low frequency domain, to a dynamic behaviour that is not stackable with another design, even in the presence of strong aleatory uncertainties. This assessment supports the conjecture that guitar brace design choices have a greater impact than material variability where guitar soundboard dynamics are concerned. More generally, these results illustrate the usefulness of detailed physics-based models in the understanding, design and making of guitars.